On the possibility of electric transport mediated by long living intrinsic localized solectron modes - Cantu Ros, O. G. (2014)
We consider a polaron Hamiltonian in which not only the lattice and the electron-lattice interactions, but also the electron hopping term is affected by anharmonicity. We find that the one-electron ground states of this system are localized in a wide range of the parameter space. Furthermore, low energy excited states, generated either by additional momenta in the lattice sites or by appropriate initial electron conditions, lead to states constituted by a localized electron density and an associated lattice distortion, which move together through the system, at subsonic or supersonic velocities. Thus we investigate here the localized states above the ground state which correspond to moving electrons. We show that besides the stationary localized electron states (proper polaron states) there exist moving localized solectron states which can be easily excited. The evolution of these localized states suggests their potential as new carriers for fast electric charge transport.